Приложение эргодической теории к исследованию краевой задачи с периодическим операторным коэффициентом - Бойчук, А.А.; Покутный, А.А. (Український математичний журнал, 2013)
Встановлено необхiднi та достатнi умови розв’язностi сiм’ї диференцiальних рiвнянь iз перiодичним операторним коефiцiєнтом i перiодичною крайовою умовою з допомогою поняття вiдносного спектра лiнiйного обмеженого оператора в банаховому просторi й ергодичної теореми. Показано, що при виконаннi умови iснування такi перiодичнi розв’язки будуються з використанням одержаної у цiй статтi формули для узагальнено-оберненого оператора до лiнiйного обмеженого. We establish necessary and sufficient conditions for the solvability of a family of differential equations with periodic operator coefficient and periodic boundary conditions by using the notion of relative spectrum of a linear bounded operator in a Banach space and the ergodic theorem. It is shown that if the existence condition is satisfied, then the required periodic solutions can be constructed by using the deduced formula for the generalized inverse operator of a linear bounded operator.